The impact of the "Arab Spring" on the domestic political situation in France (2011-2024) - Rebizov, Nikita Ilich; Karpunina, Polina Sergeevna (Конфликтология / nota bene, 2025)
The relevance of this study is due, first, to the increase in social tensions within French society against the backdrop of internal political instability; secondly, to the growth of internal political instability in the countries of the Middle East and Africa in the context of delayed consequences of the «Arab Spring». The object of this study is internal political changes in France (2011-2024). The subject of the study is the influence of the «Arab Spring» on the domestic political situation in France (2011-2024). The aim of this study is to determine the impact of the «Arab Spring» on the domestic political situation in France. In the course of this study, the authors had the following tasks: to study the history of the «Arab Spring» and determine its impact on countries of the Middle East and Africa, to determine the level of influence of the «Arab Spring» on the domestic political situation in France. This study is based on the theory of neorealism in international relations, which implies the permanent struggle of states for their own national interests. Armed conflicts are often the instruments of this struggle, owing to the lack of a central authority capable of controlling the activities of States in the international arena. The main conclusions of the study are definition the "Arab Spring" as a key destabilizing factor of the domestic political situation in the countries of the Middle East and Africa; identification of increased terrorist activity in Syria and the Sahel states as a delayed consequence of the "Arab Spring"; identification of an increasing number of refugees from the territory of the Syrian Arab Republic and the Sahel states as a key "tool" of impact of the «Arab Spring» to the domestic situation in France. The scientific novelty of this study is based on the findings of this study.